2011
DOI: 10.1155/2011/424203
|View full text |Cite
|
Sign up to set email alerts
|

The LLNA: A Brief Review of Recent Advances and Limitations

Abstract: Allergic contact dermatitis is the second most commonly reported occupational illness, accounting for 10% to 15% of all occupational diseases. This highlights the importance of developing rapid and sensitive methods for hazard identification of chemical sensitizers. The murine local lymph node assay (LLNA) was developed and validated for the identification of low molecular weight sensitizing chemicals. It provides several benefits over other tests for sensitization because it provides a quantitative endpoint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 96 publications
(100 reference statements)
2
84
0
Order By: Relevance
“…Another crucial factor affecting the variability is the choice of the vehicle. Vehicle impact has already been explored in some detail, for example by Jowsey et al (2008), who reported a tendency toward underestimated potency for aqueous vehicles or propylene glycol, and has been briefly reviewed (Anderson et al, 2011). Our analysis supports the general view that repeat testing with different vehicles leads to more variable EC3 values than repeat testing with the same vehicle.…”
Section: Conflict Of Interestsupporting
confidence: 80%
“…Another crucial factor affecting the variability is the choice of the vehicle. Vehicle impact has already been explored in some detail, for example by Jowsey et al (2008), who reported a tendency toward underestimated potency for aqueous vehicles or propylene glycol, and has been briefly reviewed (Anderson et al, 2011). Our analysis supports the general view that repeat testing with different vehicles leads to more variable EC3 values than repeat testing with the same vehicle.…”
Section: Conflict Of Interestsupporting
confidence: 80%
“…It is well established that non-sensitizing irritants can induce proliferation in the LLNA, thereby confounding the ability to distinguish between irritants and sensitizers. However, responses that exceed a stimulation index (SI) of 3-fold over control are typically associated with sensitizers and not irritants (Anderson et al, 2011), although exceeding an SI of 3 does not confirm that a chemical is truly a sensitizer. Although hypersensitivity to implanted titanium has been documented in humans (Müller & Valentine-Thon, 2006) and is consistent with a possible systemic hypersensitivity response to nano-TiO 2 in the present study, further study is warranted to more clearly delineate the irritant vs systemic hypersensitivity of nano-TiO 2 following parenteral administration.…”
Section: Discussionmentioning
confidence: 99%
“…Currently preclinical allergic risk assessments rely on animal-based tests [18]. However, this approach has been criticized for providing poor clinical relevance due to species variation in immune responses and drug metabolism [19][20][21].…”
Section: Current Challenges and Issuesmentioning
confidence: 99%